Phase Conjugation Using Four-Wave Mixing in Fast Green FCF Dye-Doped Gelatin Film. (31st January 2010) - Majles Ara, M. H.; Mehrabani, S.; Malekfar, R.
Abstract : We present optical phase conjugation based on the degenerate four-wave mixing (DFWM) arrangement in gelatin films doped with acid blue 3 dye (FAST GREEN FCF) using He-Ne laser of total power 50 mW. Various parameters which influence the phase-conjugate (PC) signal during the DFWM process were studied (angle of between the forward pump and the probe beam, transition of gelatin film, reflectivity as a function of forward and backward beam). A maximum phase-conjugate beam reflectivity of about 0.02% has been observed in these dye-doped gelatin films. PACS: 42.65.-k, 42.65.Hw.